KEMAMPUAN SISWA MEMECAHKAN MASALAH DENGAN METODE MIND MAPPING DI KELAS BILINGUAL SMP NEGERI 1 PALEMBANG - Pratiwi, Weni Dwi; Aisyah, Nyimas; Purwoko (Mathematics Education Journal, 2013)
This research is motivated by the low ability of students to solve math problems. This is due to the lack of ability of students in understanding the problem and carrying out up the problem-solving plan with the right method. This study aims to determine the ability of students solving mathematical problems with the use of mind mapping method in bilingual class SMP Negeri 1 Palembang and get some description of the quality of mind mapping used by students in solving problem-solving problems. The subjects of this study are 30 students of class VII.2 SMP Negeri 1 Palembang. This research method is descriptive research. Based on the results of research and discussion it can be concluded that the quality of mind map categorized good with the average value of 76.11 while the ability of students solving mathematical problems with mind mapping method as a whole is categorized good that is equal to 78.93. While the ability of students to solve the problem with mind mapping method as a whole is as much as 35.71% of students in very good category. Based on the results of these studies, it is expected to the school to facilitate teachers and students to be able to carry out learning that can improve the ability to solve mathematical problems and always open with innovative new methods or techniques that drive that ability. DOI: https://doi.org/10.22342/jpm.7.2.3883.